Coconut Agribusiness Supply Chains and the Potential for Closed-Loop Models in North Sulawesi - Pakasi, Caroline B. D.; Benu, Noortje Marsellanie; Sondakh , Mex Frans Lodwyk (Sam Ratulangi University, 2025)
Abstract. Coconut is a key smallholder crop in North Sulawesi Province, Indonesia, yet the agribusiness system remains characterised by low on-farm value addition, quality losses and underutilised by-products. A closed-loop supply chain model, which integrates forward flows of primary products with reverse flows of by-products and residues, has been proposed as a way to improve efficiency, market access and price incentives for farmers. This study analyses the coconut agribusiness supply chain in two major producing districts, Minahasa Tenggara and Minahasa Selatan, focusing on current configurations and the potential implementation of a closed-loop model. An applied case-study design was used, combining secondary data with primary data collected through questionnaires and interviews with farmers, traders, micro, small and medium enterprises (MSMEs), processing companies and supporting institutions between March and October 2024. Qualitative mapping and descriptive quantitative analysis were employed to examine supply chain structure, coordination, by-product utilisation, market access and price incentives. The results show that Minahasa Tenggara still operates a conventional, trader-driven supply chain with limited processing and minimal integration of by-products, whereas Minahasa Selatan exhibits emerging closed-loop features through partnership schemes linking farmer groups, processing companies and MSMEs, including the utilisation of husk, shell and coconut water for cocopeat, coir products, charcoal, briquettes and liquid organic fertiliser. These arrangements provide a foundation for improved market access and potentially better price incentives for farmers, but benefits remain uneven and depend on institutional support and the strengthening of farmer organisations and MSMEs. Keywords: coconut; closed-loop supply chain; agribusiness; by-products; smallholder farmers.